A Single Nonlinear Current Control for PWM Rectifier Robust to Input Disturbances and Dynamic Loads. (19th November 2017) - Visairo-Cruz, Nancy; Núñez-Gutiérrez, Ciro; Alcázar, Eliseo; Rodríguez, Elías
Abstract : The requirements of PWM rectifiers for delivering power to motor drives include power factor correction and output voltage regulation even when strong variations such as voltage sags and dynamic load transients occur simultaneously. To achieve these objectives, the classic approach is to use a two-loop controller with its d -q model. In this paper, the authors propose a simplified approach to address that problem by using a feedback linearization-based nonlinear controller using only a single-loop current control and avoiding d -q modeling to reduce processing stages. To demonstrate the feasibility of this approach, several simulations are presented considering a 1.5 kW PWM rectifier.